Analysis of the Influence of Managerial Ownership, Collateralizable Assets, and Sales Growth on Dividend Policy - Suharmadi SUHARMADI; Suripto SURIPTO (Indonesia Strategic Sustainability, 2023)
This study aims to determine the effect of Managerial Ownership (MO), Collateralizable Assets (CA) and Sales Growth (SG) on Dividen Policy (DPR). The population of this research are manufacturing companies in the consumer goods sector which are listed on the Indonesia Stock Exchange (IDX) in the period 2015 – 2019. Company samples obtained from the selection are 18 companies so that the sample is 72 data. The result found that Managerial Ownership (MO), Collateralizable Assets (CA) and Sales Growth (SG) are simultaneous effect on Dividen Policy (DPR). Partially Managerial Ownership (MO) and Collateralizable Assets (CA) have no effect on Dividen Policy (DPR). Meanwhile Sales Growth (SG) has a positive and significant effect on Dividen Policy (DPR).